THE EXISTENCE OF TRADITIONAL BIRTH ATTENDANTS (DUKUN PARAJI) IN THE PRACTICE OF BIRTH ASSISTANCE SERVICES IN BOGOR REGENCY: EKSISTENSI DUKUN PARAJI DALAM PRAKTIK PERTOLONGAN LAYANAN PERSALINAN DI KABUPATEN BOGOR (Jurnal Gizi Masyarakat Indonesia (The Journal of Indonesian Community Nutrition), 2024)
Introduction: The role of traditional birth attendants, known as "dukun paraji," remains significant in childbirth assistance, particularly in Bogor Regency, West Java. Objective: This study aims to explore the existence and practices of dukun paraji in childbirth assistance and their impact on maternal and infant health in the region, with the hope of providing a deeper understanding of traditional healthcare dynamics within the context of the modern healthcare system. Method: A quantitative survey was conducted with 235 mothers retrospectively to determine the involvement of dukun paraji in the childbirth process. Results: Findings reveal that 31.4% of mothers in Bogor Regency utilized the services of dukun paraji during childbirth, while the remainder received assistance from healthcare professionals. This suggests that while traditional birth attendants still play a significant role in childbirth assistance, the majority of the population prefers assistance from healthcare professionals. Conclusion: Despite the prevalence of healthcare professionals, the existence of dukun paraji in childbirth assistance remains significant in Bogor Regency. This underscores the importance of preserving cultural heritage while ensuring universal access to safe healthcare. Increasing awareness of the importance of safe and accessible maternal healthcare in communities needs to be continually promoted. Efforts to strengthen collaboration between dukun paraji and healthcare professionals in providing safe childbirth services are essential. Additionally, inclusive and comprehensive maternal health education should be enhanced to ensure communities have sufficient knowledge to make informed choices regarding maternal care.